كفاءة الأستاذ وعلاقتها بجودة العملية التعليمية. - دراسة ميدانية لعينة من الطلبة بجامعة باتنة - جلول, أحمد; بشقة, عز الدين (جامعة الوادي - University of Eloued, 2020)
لا يختلف اثنان في صحة تكامل القواعد الأساسية الثلاث " المعلم – المتعلم- المنهاج" في ترسيخ أهداف المناهج التربوية وتحقيق الأهداف المسطرة من خلالها بداية من المراحل الأولى للتعلم إلى غاية أكبر مرحلة قد يصل إليها طالب العلم، و إن كان التركيز متصل في الأبحاث التربوية و التعليمية بالمراحل الأولى على الأحداث و علاقتهم بتقمص الشخصية المتزنة لدى المعلم منذ الطفولة حتى سن المراهقة إلا أن هناك من الدراسات التي تناولت أثر الفعل التربوي التعليمي للأستاذ الجامعي و أثره على استقرار النظام القيمي لدى طلبة الجامعة تكاد تشح تحت ذريعة تجاوزهم سن المراهقة. فالانتقادات الموجهة نحو هذا الاتجاه تتخذ من الخلل الحاصل بين المرتبة العلمية والمستوى الاجتماعي لدى هذا النخبة (الأستاذ الجامعي) و شذوذه عن القيم المعرفية و الاجتماعية قاعدة للتهرب من الضوابط الاجتماعية والأخلاقية بدعوى أن الفئة لا تمثلها أحسن تمثيل و بالتالي لا جدوى من الإقتداء بها. ومن أجل الوصول إلى استجلاء هذه الإشكالية واستكشاف المحددات المشكلة للفعل التربوي التعليمي لدى الأستاذ الجامعي وعلاقتها بالجودة التعليمية، جاءت هذه الدراسة لتجيب على فرضيات تتعلق بأثر ركائز الفعل التربوي التعليمي الفعال من كفاءة معرفية وسلوكية وأدائية من أجل تجويد الفعل الديداكتيكي لما له من علاقة مباشرة بالجودة التعليمية Firstly, There is no difference in the validity of the integration of the three basic rules of "teacher - learner - curriculum" in the consolidation of the objectives of educational curricula and achieve the objectives set through it from the early stages of learning to the greatest stage may reach the student science, if the focus is connected to education a research and education in the first stages on events and their relation to the characterization of the balanced character of the teacher from childhood to adolescence, however there are studies that dealt with the impact of the educational action of the university professor and its impact on the stability of the value system of university students almost under the pretext of over the age of adolescence. Secondly, the Criticism towards this trend takes place in the imbalance between the scientific rank and the social level of this elite (the university professor) and its deviation from the cognitive and social values as a basis for evading social and moral controls on the grounds that the class does not represent the best representation and there forfeits useless to follow them. Finally, In order to arrive at the clarification of this problem and to explore the determinants of the educational and education al behavior of the university professor and its relation to educational quality, this study is based on hypotheses related to the effect of the pillars of the educational act of effective educational efficiency of cognitive, behavioral and performance in order to improve the act didactics because of its direct relationship Educational quality
The professor's efficiency and its relation to the quality of the educational process A field study of a sample of students at the University of Batna
مقال بمجلة السراج في التربية وقضايا المجتمع . مج 04 ع01. أوت 2020 . جامعة الوادي
Keywords: الكفاءة، الأستاذ الجامعي، جودة العملية التعليمية; efficiency, university professor, quality of the education alprocess (do not exceed 5 keywords)